Application of CRISPR/Cas9 technology in forages. Issue 4 (2nd January 2023) - Bao, Qinyan; Wolabu, Tezera W.; Zhang, Qian; Zhang, Tian; Liu, Zhipeng; Sun, Juan; Wang, Zeng‐Yu
Abstract: Genome editing is an advanced genetic modification tool that facilitates the removal, insertion, or substitution of nucleotides in the genome of an organism for mutation induction. CRISPR/Cas9 (clustered regularly interspaced short palindromic repeats/CRISPR‐associated protein 9) is the most widely used genome editing tool that can precisely modify the specific sequence of a genome. Significant progress has been made in the use of CRISPR/Cas9 for the genetic improvement of food crops. However, in forage crops, the use of CRISPR/Cas9 is still in the infant stage with limited understanding and application. This article reviews current advances in the establishment and application of the CRISPR/Cas9 system in alfalfa, summarizes the application of CRISPR/Cas9 in several other forage legume and grass species, and discusses the prospects of CRISPR/Cas9 in the genetic improvement of forage crops. Abstract : Alfalfa plants were obtained by genome editing of the Stay‐green ( MsSGR ) gene and by RNA interference (RNAi) downregulation of MsSGR . The genome‐edited alfalfa showed a more consistent greenish appearance than the RNAi plants after dark treatment.